2021
DOI: 10.2147/jhc.s337111
|View full text |Cite
|
Sign up to set email alerts
|

PRRC2A Promotes Hepatocellular Carcinoma Progression and Associates with Immune Infiltration

Abstract: Purpose Hepatocellular carcinoma (HCC) has high morbidity and poor prognosis due to the propensity of recurrence and metastasis. Emerging studies have confirmed that proline-rich coiled-coil2A (PRRC2A) plays a crucial role in tumorigenesis and immunoregulation. However, its expression status and biological functions in HCC remain poorly documented. Methods The presence and prognostic value of PRRC2A were determined by a tissue microarray (TMA) cohort and multiple databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 50 publications
1
11
0
1
Order By: Relevance
“…and our results suggested a higher infiltration rate of resting myeloid DCs in the high-risk group, which may contribute to a poorer immune response. The data from the ESTIMATE method showed that the high-risk group had a higher immune score, which could represent the higher levels of immune cell infiltration in the TME and was consistent with previous studies (58,59). However, our study showed that high risk patients had poor immunotherapy response and high immune cell infiltration levels did not mean a better immunotherapy response.…”
Section: Discussionsupporting
confidence: 91%
“…and our results suggested a higher infiltration rate of resting myeloid DCs in the high-risk group, which may contribute to a poorer immune response. The data from the ESTIMATE method showed that the high-risk group had a higher immune score, which could represent the higher levels of immune cell infiltration in the TME and was consistent with previous studies (58,59). However, our study showed that high risk patients had poor immunotherapy response and high immune cell infiltration levels did not mean a better immunotherapy response.…”
Section: Discussionsupporting
confidence: 91%
“…Although their molecular functions are not completely understood, the PRRC2 proteins appear to have clinical relevance. Mutations in PRRC2A are associated with multiple cancers, including non-Hodgkin-Lymphoma ( 13 ), lung cancer ( 14 ), ER-positive breast cancer ( 15 ) and hepatocellular carcinoma, where they promote progression and immune infiltration ( 16 ). A PRRC2B-ALK gene fusion was found in an aggressive malignant neoplasm ( 17 ), and PRRC2C was found to have a different pattern of alternative splicing in non-small lung tumors compared to healthy lung ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…1A-B). Since these proteins have been linked to disease (16–19,22), we decided to study them in detail. We confirmed that PRRC2B and PRRC2C interact with eIFs by co-immunoprecipitation with endogenous eIF3B, eIF4G1 and eIF4E (Figure 2G).…”
Section: Resultsmentioning
confidence: 99%
“…Although their molecular functions are not completely understood, the PRRC2 proteins appear to have clinical relevance. Mutations in PRRC2A are associated with multiple cancers, including non-Hodgkin-Lymphoma (16), lung cancer (17), ER-positive breast cancer (18) and hepatocellular carcinoma, where they promote progression and immune infiltration (19). A PRRC2B-ALK gene fusion was found in an aggressive malignant neoplasm (20), and PRRC2C was found to have a different pattern of alternative splicing in non-small lung tumors compared to healthy lung (21).…”
Section: Introductionmentioning
confidence: 99%